Biological and economic potential of autumn-planted sugarcane (Saccharum officinarum) in sole and inter cropping system under varying moisture regimes - GULATI, J M; NAYAK, B C; MISHRA, M M (The Indian Journal of Agricultural Sciences, 2013)
A study was conducted during 1991-92 to 1993-94 at Sambalpur, Orissa for biological and economic potential of autumn planted ’Co 6304’ sugarcane (Saccharum officinarum L.) with treatment combinations of 5 cropping systems (sugarcane sole, wheat (Triticum aestivum L. emend. Fiori & Paol.) sole, rapeseed (Brasica campestris L. var toria) sole, sugarcane + wheat, sugarcane + rapeseed) and 3 moisture regimes (0.8, 1.0, 1.2 IW:CPE ratio). Cane yield of the sole sugarcane was the maximum (107.25 tonnes/ha) which declined by 16.6 and 8.3%Â·due to intercropping of wheat and rapeseed, respectively. Frequently irrigated plots at 1.2 IW:CPE ratio (50 mm CPE) recorded the maximum cane yield (106.03 tonnes/ha). Its yield reduced by 7.9 and 13.9% due to sub optimal moisture regime of 1.0 (60 mm CPE) and moderate moisture regime of 0.8 (75 rom CPE) IW:CPE ratio, respectively. The maximum net monetary return of Rs 22 493/ha was obtained from sugarcane + rapeseed system at 1.2 IW:CPE ratio with greater biological efficiency as indicated by maximum LER(1.90), benefit: cost ratio (l.57) and water-use efficiency (Rs 1 28/ha-cm). Sole sugarcane was at par with sugarcane + rapeseed system in respect of net monetary returns.